2017
DOI: 10.1002/cne.24173
|View full text |Cite
|
Sign up to set email alerts
|

V1 connections reveal a series of elongated higher visual areas in the California ground squirrel, Otospermophilus beecheyi

Abstract: For studies of visual cortex organization, mouse is becoming an increasingly more often used model. In addition to its genetic tractability, the relatively small area of cortical surface devoted to visual processing simplifies efforts in relating the structure of visual cortex to visual function. However, the nature of this compact organization can make some comparisons to the much larger non-human primate visual cortex difficult. The squirrel, as a highly visual rodent offers a useful means for better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 87 publications
1
14
0
Order By: Relevance
“…Additionally, when injections within the superior colliculus were separate and non‐overlapping, the patches of cortical label were also non‐overlapping, providing evidence for visuotopically organized fields. Recent studies in ground squirrel have suggested that multiple topographically organized cortical fields are represented between area 18 and TP (Negwer et al ., ). It is likely that the patchy pattern of SC projecting cells within OTc in our current study reflects a similar organization scheme in the grey squirrel.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Additionally, when injections within the superior colliculus were separate and non‐overlapping, the patches of cortical label were also non‐overlapping, providing evidence for visuotopically organized fields. Recent studies in ground squirrel have suggested that multiple topographically organized cortical fields are represented between area 18 and TP (Negwer et al ., ). It is likely that the patchy pattern of SC projecting cells within OTc in our current study reflects a similar organization scheme in the grey squirrel.…”
Section: Discussionmentioning
confidence: 97%
“…For instance, early reports have combined OTc and OTr into a single area, area 19 (Hall et al ., ; Kaas et al ., ; Wong & Kaas, ); while others have included the presence of a middle lateral (ML) and lateral (L) areas between an area V3 and TP (Paolini & Sereno, ). A recent study in California ground squirrels has suggested another pattern of cortical organization (Negwer et al ., ), which includes ML and L, but includes additional areas separating these structures form V1. This organization scheme a long cortical area, V3, which runs along the central majority of V2 with an area V3a, and P located along the most rostromedial or caudolateral portions of V2, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Visual perception occurs through a complex network of cortical processing that relies on driving, modulating, and integrating interconnectivity with subcortical visual structures as studied extensively in rodents (Guillery & Sherman, ; Krubitzer, Campi, & Cooke, ; Marshel, Garrett, Nauhaus, & Callaway, ; Niell, ; Negwer, Liu, Schubert, & Lyon, ; Seabrook, Burbridge, Crair, & Huberman, ), carnivores (Reid & Alonso, ; Liu, Hashemi‐Nezhad, & Lyon, ; Hashemi‐Nezhad & Lyon, ) nonhuman primates (Felleman & Van Essen, ; Casagrande, ; Lyon et al, ; Casagrande, Sáry, Royal, & Ruiz, ; Kaas, ), and close relatives such as the tree shrew (Casagrande & Harting, ; Lyon, Jain, & Kaas, ; Casagrande, Xu, & Sáry, ). The lateral geniculate nucleus, the superior colliculus and the pulvinar nucleus, are among the most studied subcortical visual regions, having been subject to decades of anatomical and functional investigation by Vivien Casagrande and her colleagues in tree shrew (i.e., Casagrande, Harting, Hall, Diamond, & Martin, ; Lyon, Jain, & Kaas, , b; Vanni, Thomas, Petry, Bickford, & Casanova, ) and primate (i.e., Fitzpatrick, Carey, & Diamond, ; Lachica & Casagrande, ; Stepniewska & Kaas, ; Xu et al, ; Nassi, Lyon, & Callaway, ; Imura & Rockland, ; Kaas & Lyon, ; Lyon, Nassi, & Callaway, ; Purushothaman, Marion, Li, & Casagrande, ; Cerkevich, Lyon, Balaram, & Kaas, ), and by many others in rodent (i.e., Lysakowski, Standage, & Benevento, ; Sanderson, Dreher, & Gayer, ; Van Hooser & Nelson, ; Marshel, Kaye, Nauhaus, & Callaway, ; Cruz‐Martín et al, ; Tohmi, Meguro, Tsukano, Hishida, & Shibuki, ; Roth et al, ; Seabrook et al, ; Zhou, Maire, Masterson, & Bickford, ; Zhou, Masterson, Damron, Guido, & Bickford, ).…”
Section: Introductionmentioning
confidence: 99%